2018
DOI: 10.1371/journal.pone.0196022
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic score to predict mortality during TB treatment in TB/HIV co-infected patients

Abstract: BackgroundEstimating mortality risk during TB treatment in HIV co-infected patients is challenging for health professionals, especially in a low TB prevalence population, due to the lack of a standardized prognostic system. The current study aimed to develop and validate a simple mortality prognostic scoring system for TB/HIV co-infected patients.MethodsUsing data from the CDC’s Tuberculosis Genotyping Information Management System of TB patients in Texas reported from 01/2010 through 12/2016, age ≥15 years, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
8
10
0
Order By: Relevance
“…Nevertheless, this condition can also be due to the non-specific symptoms and broad-spectrum immune response among patients with TB-HIV, which may produce false negative sputum smear results among such patients(31-35). These findings were concordant with that of Nguyen et al and Nik Nor Ronaidi et al (16,19). Others have however showed that positive sputum smear is significantly associated with unsuccessful TB treatment outcome (1,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, this condition can also be due to the non-specific symptoms and broad-spectrum immune response among patients with TB-HIV, which may produce false negative sputum smear results among such patients(31-35). These findings were concordant with that of Nguyen et al and Nik Nor Ronaidi et al (16,19). Others have however showed that positive sputum smear is significantly associated with unsuccessful TB treatment outcome (1,29).…”
Section: Discussionsupporting
confidence: 93%
“…TB infection with late presentation and HIV diagnosis are further risk factors for unsuccessful TB treatment outcome among patients with TB-HIV (13)(14)(15). Other than that, patients with positive sputum culture upon TB diagnosis are at higher risk for unsuccessful TB treatment outcome (16).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this condition can also be due to the non-specific symptoms and broadspectrum immune response among patients with TB-HIV co-infection, which may produce false negative sputum smear results among such patients [24,[39][40][41][42]. These findings were concordant with that of Nguyen et al and Nik Nor Ronaidi et al [19,27]. Others have however showed that positive sputum smear is significantly associated with unsuccessful TB treatment outcome [1,37].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, positive sputum culture upon diagnosis was significantly associated with unsuccessful TB treatment outcome. This finding was supported by similar findings by Prado et al, Nguyen et al and Swaminathan et al [1,19,32]. Patients with TB-HIV co-infection with positive sputum culture may have higher TB bacterial loads, which may thus worsen the prognosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation